2014
DOI: 10.4077/cjp.2014.bab171
|View full text |Cite
|
Sign up to set email alerts
|

The Stimulating Effects of Nitric Oxide on Intermediate Conductance Ca^(2+)-Activated K^+ Channels in Human Dermal Fibroblasts through PKG Pathways but not the PKA Pathways

Abstract: Nitric oxide (NO) is produced by nitric oxide synthase (NOS) in dermal fibroblasts and is important during wound healing. Intermediate conductance Ca²⁺-activated K+ (IK; IK1; KCa3.1; IKCa; SK4; KCNN4) channels contribute to NOS upregulation, NO production, and various NO-mediated essential functions in many kinds of cells. To determine if the action of NO is linked to IK channel regulation in human dermal fibroblasts, we investigated the expression of IK channels in the cells and the effects and mechanisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…The K + currents that were recorded by whole-cell mode patch clamping in our experiments showed the characteristic features of BKCa currents that have been previously reported in other cells, namely, inhibition by IBTX (a specific BKCa blocker), activation at −40 mV, non-inactivating, oscillating properties when exposed to strong depolarization, and outward rectification in the I-V curve. These results for HCFs were similar to previous results pertaining to BKCa currents in human dermal fibroblasts, 19 vascular smooth muscle cells, 20 and endothelial cells. 21 However, KCa channels are found in cardiac fibroblasts but not in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 91%
“…The K + currents that were recorded by whole-cell mode patch clamping in our experiments showed the characteristic features of BKCa currents that have been previously reported in other cells, namely, inhibition by IBTX (a specific BKCa blocker), activation at −40 mV, non-inactivating, oscillating properties when exposed to strong depolarization, and outward rectification in the I-V curve. These results for HCFs were similar to previous results pertaining to BKCa currents in human dermal fibroblasts, 19 vascular smooth muscle cells, 20 and endothelial cells. 21 However, KCa channels are found in cardiac fibroblasts but not in cardiomyocytes.…”
Section: Discussionsupporting
confidence: 91%
“…However, in the present study, we show that KCa channels also contribute to cutaneous blood flow regulation during low-dose NO ad- ministration in young adults ( Fig. 2A), which may be associated with NO-induced activation of KCa channels as reported in vitro (3,42). Since activation of KCa channels located on endothelial cells induces endothelium-dependent hyperpolarization and thus vasodilation (12), our results suggest that endothelium-derived relaxing factor may contribute to the regulation of cutaneous blood flow with low doses of SNP administration.…”
Section: Discussionsupporting
confidence: 72%
“…Furthermore, NO may induce cutaneous vasodilation by influencing endothelium-derived relaxing factors that include cyclooxygenase (COX) and endothelium-dependent hyperpolarization, the latter of which is mediated through calcium-activated potassium (KCa) channels (12). Indeed, both KCa channels and COX contribute to cutaneous blood flow regulation in humans in vivo (5,7,8,33,36) and NO can activate KCa channels (3,42) and COX (48) as suggested in cultured cell studies. However, whether KCa channels and COX contribute to cutaneous blood flow regulation during exogenous NO administration remains unclear in humans.…”
mentioning
confidence: 99%
“…However, it exhibited a steeply voltage-dependent activation at –40 mV, which is not consistent with KCa3.1. Finally, a study of single-channel activity in human dermal fibroblasts showed that activity was increased by the NO donor, S-nitroso- N -acetylpenicillamine (SNAP) in cell-attached patches, and by applying cGMP + PKG to the cytoplasmic face of inside-out patches ( 60 ). The channel was blocked by 10 μM clotrimazole, was depolarization activated at about –40 mV, and had a large single-channel conductance (116 pS reported, >150 pS in some recordings); properties that are inconsistent with KCa3.1.…”
Section: Discussionmentioning
confidence: 99%